Making a difference: The role of the Māori administrator in Universities - Smith, Tania (Te Kaharoa, 2012)
<span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">The<em style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;"> Tertiary Education Strategy 2010 – 2015<span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;"> in Aotearoa/New Zealand states that the Government aims to ‘increase the number of Māori students achieving at the higher level’ (Tertiary Education Commission 2010, p10). For this to be achieved universities need to play their part in assisting Māori students to progress beyond the undergraduate degree and into postgraduate study. <span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">Universities take their origins from western European values, ideals and world view which are reflected in the curriculum, management systems and processes. It is predicated that by 2020 over half the tertiary student population will be Māori due to a youthful Māori population (Department of Labour, 2008). This will be a challenge for universities. Therefore, the role of a Māori administrator within the university system becomes critical in being able to provide useful insight to the university on how to retain Māori students in this changing environment. <span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">This paper draws on my Master of Philosophy research. It will critically examine the role Māori administrator’s play in the recruitment and retention of Māori students in universities in Aotearoa/New Zealand including culturally specific pastoral care, accurate course advice, information on degree requirements, appropriate learning pathways for students and supporting academic staff to track student progress through to completion. These additional responsibilities, often unrecognised by the university, demonstrates the important role a Māori administrator can make in retaining Māori students in the academy.